Different processes for translating expressive versus informative texts? A computer-assisted study of professionals' English–Chinese translation. (15th December 2020) - Zheng, Jianwei; Fan, Wenjun
Abstract: This article explores the differences of translation processes for expressive and informative texts by professional translators primarily by triangulating pausing and revision data retrieved by Keystroke logging experiment and rational report thereof via questionnaire survey and interview. The article discovers that in terms of temporal distribution, the drafting of informative text accounts for a larger proportion of time, while orientation and checking accounts for a smaller proportion compared with those of expressive texts. At orientation interval, translators come to fully understand the source expressive text at the very beginning, while generally conducting syntactic analysis of and re-sequencing the semantic component of source text in target language in translating informative text. At drafting interval, structural modification frequency word rate (MWR) in translating the expressive text is larger than that in translating the informative texts, while spelling and lexical MWRs of both texts are similar. At checking interval, both texts hardly see any structural modification, but lexical MWR for the former is much bigger than that for the latter. These data, along with pausing and revision rational report, suggest the priority of familiarity with standardized grammar and expertise in specialized field for translating informative text, and the importance of embedded reading and writing training for translating expressive text.